(untitled) (Fountain Journal of Natural and Applied Sciences, 2024)
Malaria vector abundance has been linked to certain agricultural practices. This work examined the impact of the agricultural practice of irrigation on the composition and seasonal distribution of malaria vectors in agrarian communities of Kano state. Longitudinal data collection was done four times a year, corresponding to different transmission seasons from early rains to late rainy season, early dry season to late dry season. Indoor-biting adult mosquitoes were collected using standard pyrethrum spray collection (PSC) techniques. Female Anopheles mosquitoes collected from houses were morphologically identified to species level. Molecular characterisation of the members of the Anopheles gambiae complex was carried out using PCR technique. Two thousand four hundred fifty-two (2452) adult female Anopheles species were collected throughout the study period. The Large Irrigation (LIC) and Urban Irrigation Communities (UIC) had a higher mean abundance of female Anopheles mosquitoes across seasons. There was a significant difference in the mean adult mosquito catch across the season (F =113.49, p≤0.001) and across the three communities (F = 44.73; p ≤0.001). Anopheles gambiae sl. was the most encountered among the four species, with a mean abundance of 11.94±11.76, 5.39±7.45 and 2.58 ±3.41 for LIC, UIC and NIC, respectively. Molecular characterisation of An. gambiae s.l. by PCR showed the presence of three sibling species, An. coluzzi, An. gambiae ss and An. arabiensis. An. Coluzzi was significantly more abundant across the three communities during the wet and dry seasons. The predominance of this species has implications for malaria control. This study shows that irrigation is likely to influence mosquito breeding, thus exposing community members to a higher risk of being bitten by infected vectors. A review of the ecology of Anopheles species, especially in urban environments, is needed, considering the current abundance of malaria vectors in the urban community. Keywords: Seasonal, Abundance, Composition, Anopheles species, Irrigation, Urban